2021
DOI: 10.1038/s41434-021-00258-6
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of RPGR expression in vivo using CRISPR/Cas9 gene editing

Abstract: Mutations in the gene for Retinitis Pigmentosa GTPase Regulator (RPGR) cause the X-linked form of inherited retinal degeneration, and the majority are frameshift mutations in a highly repetitive, purine-rich region of RPGR known as the OFR15 exon. Truncation of the reading frame in this terminal exon ablates the functionally important C-terminal domain. We hypothesized that targeted excision in ORF15 by CRISPR/Cas9 and the ensuing repair by non-homologous end joining could restore RPGR reading frame in a porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The same approach has been used successfully in human cells to resolve the RHO gene mutation. This study confirms CRISPR/Cas9 as an effective system to target gene/alleles in a well-organized way indicating that it may be cast off for the treatment of RP and further dominant human genetic disorders [ 83 ].…”
Section: Crispr/cas9 Is a Promising Strategy To Restore The Blindnesssupporting
confidence: 65%
“…The same approach has been used successfully in human cells to resolve the RHO gene mutation. This study confirms CRISPR/Cas9 as an effective system to target gene/alleles in a well-organized way indicating that it may be cast off for the treatment of RP and further dominant human genetic disorders [ 83 ].…”
Section: Crispr/cas9 Is a Promising Strategy To Restore The Blindnesssupporting
confidence: 65%
“…Rhodopsin (RHO) gene mutations had been widely used in mice and dogs as animal models of autosomal dominant RP [ 53 ]. Gumerson et al established an X-linked RP animal model, which was a mouse model of retinitis pigmentosa GTPase regulator (RPGR) deficiency similar to human RP3 [ 54 ]. Researchers used drug injection to create animal models of RP.…”
Section: Retinal Disordersmentioning
confidence: 99%
“…Superior effects of rAAV2tYF-GRK1-hRPGRco and clues for reaching the appropriate dose for human studies were demonstrated [77]. Also, using CRISPR/Cas9 for repairing the RPGR gene with a pattern DNA strand in the process of HDR (homology-directed repair) in the RPGR -/y mouse model has been associated with good therapeutic effects for 6 to 12 months after treatment [78,79].…”
Section: Preclinical Gene Therapy Trials Of Xlrpmentioning
confidence: 99%